Mewartakan Sabda Allah dalam Konteks Budaya Lokal - Petrus Christologus Dogo, Lic (Sekolah Tinggi Pastoral Atma Reksa Ende, Jalan Gatot Subroto, KM 3. Tlp./Fax (0381) 250012, 2016)
One problem the Church is facing today is the question on how to meet local culture without putting faith aside. Second Vatican Council isfully aware of the problem and urges the Church to find different ways to set good dialog with local cultures. The term enculturation then becomes the main jargon in the process. All efforts made to communicate with the cultures are meant to help the faithful understand the Gospel messages and then have faith in God proclaimed by Jesus. Every Christian, the follower of Christ, has the same task to continue what Jesus has done, namely to proclaim the Good News to all people wherever the Christian is. Considering the local context will help him or her in carrying out this task effectively. Local culture is one of the many contexts which should not be neglected. As a matter of fact, a good observation and resarch on local culture will certainly help the Church in bringing the Good News more effectively to the people.